Analysis of transcriptomic responses to SARS-CoV-2 reveals plausible defective pathways responsible for increased susceptibility to infection and complications and helps to develop fast-track repositioning of drugs against COVID-19. (October 2022) - deAndrés-Galiana, Enrique J.; Fernández-Martínez, Juan Luis; Álvarez-Machancoses, Óscar; Bea, Guillermina; Galmarini, Carlos M.; Kloczkowski, Andrzej
Abstract: Background: To understand the transcriptomic response to SARS-CoV-2 infection, is of the utmost importance to design diagnostic tools predicting the severity of the infection. Methods: We have performed a deep sampling analysis of the viral transcriptomic data oriented towards drug repositioning. Using different samplers, the basic principle of this methodology the biological invariance, which means that the pathways altered by the disease, should be independent on the algorithm used to unravel them. Results: The transcriptomic analysis of the altered pathways, reveals a distinctive inflammatory response and potential side effects of infection. The virus replication causes, in some cases, acute respiratory distress syndrome in the lungs, and affects other organs such as heart, brain, and kidneys. Therefore, the repositioned drugs to fight COVID-19 should, not only target the interferon signalling pathway and the control of the inflammation, but also the altered genetic pathways related to the side effects of infection. We also show via Principal Component Analysis that the transcriptome signatures are different from influenza and RSV. The gene COL1A1, which controls collagen production, seems to play a key/vital role in the regulation of the immune system. Additionally, other small-scale signature genes appear to be involved in the development of other COVID-19 comorbidities. Conclusions: Transcriptome-based drug repositioning offers possible fast-track antiviral therapy for COVID-19 patients. It calls for additional clinical studies using FDA approved drugs for patients with increased susceptibility to infection and with serious medical complications. Highlights: Deep sampling analysis of the viral transcriptomic COVID-19 data oriented towards drug repositioning. Machine learning based samplers using the principle of biological invariance. Altered pathways reveals a distinctive inflammatory response and potential side effects of infection. The gene COL1A1 that controls collagen production seems to play a central role in the regulation of the immune system. Transcriptome-based drug repositioning offers possible fast-track antiviral therapy for COVID-19 patients.